2020
DOI: 10.1186/s12884-020-2777-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and associated factors among pregnant women in Ethiopia: facility-based cross-sectional study

Abstract: Background: Regular physical activity (PA) has health benefits, including reducing the risk of complications during pregnancy. In Ethiopia, little is known about PA status and its determinants among pregnant women. The purpose of this study was to assess PA status and associated factors among pregnant women attending antenatal care at public and private health facilities in Mekelle, Ethiopia. Methods: A facility-based cross-sectional study was conducted. Data was collected from 299 pregnant women using a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 31 publications
10
54
1
Order By: Relevance
“…This study found that about 30% of the pregnant women practiced exercise during pregnancy, nonetheless, only 11.7% among the overall sample and 37.9% among those who practiced exercise had adequate practice in accordance with the minimum recommended guidelines for this group [1,17]. This is almost similar to the ndings of two regional studies reporting about level of physical activity during pregnancy [20,30]. However, this is much lower than the practice of exercise reported in Nigeria (84.7%), Canada (29%), and Brazil (29%) in a similar population [28,31,36].…”
Section: Discussionsupporting
confidence: 76%
“…This study found that about 30% of the pregnant women practiced exercise during pregnancy, nonetheless, only 11.7% among the overall sample and 37.9% among those who practiced exercise had adequate practice in accordance with the minimum recommended guidelines for this group [1,17]. This is almost similar to the ndings of two regional studies reporting about level of physical activity during pregnancy [20,30]. However, this is much lower than the practice of exercise reported in Nigeria (84.7%), Canada (29%), and Brazil (29%) in a similar population [28,31,36].…”
Section: Discussionsupporting
confidence: 76%
“…Globally, most women do not meet the 150 min per week PA recommendation by specialised bodies and institutions. Previous studies have reported the prevalence of prenatal inactiveness with variations across countries as follows: Serbia (27.2%) [6], USA (25%) [7], China (45.15%) [8], Ethiopia (21.9%, 8.4%) [9,10], Nigeria (10.2%, 13.6%) [11,12] and Norway (14.6%) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the substantial evidence on the benefits of PA during pregnancy, studies have reported a considerable decline in PA among pregnant women in both developed [47][48][49][50] and developing countries [6,9,10,[51][52][53][54][55], with varying degrees of participation shaped by context-specific paradigms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations